Chandelier-assisted pneumatic retinopexy for rhegmatogenous retinal detachment repair in young adults - Ahmed E Habib; Ahmed A Abdel-Kader; Ayman G Elnahry (Indian Journal of Ophthalmology, 2021)
We describe the new technique of chandelier-assisted pneumatic retinopexy in repairing rhegmatogenous retinal detachments in a series of young adults. In the operating room, a 25-gauge trocar cannula is inserted at the pars plana 180° across the preoperatively detected retinal break followed by Chandelier light insertion, which is used in globe fixation and rotation. The retinal periphery is reexamined using scleral indentation and chandelier light endoillumination. Transconjunctival cryopexy is performed around the break followed by paracentesis and pure sulfur hexafluoride gas injection. Twelve eyes of 12 patients were repaired. Their mean (±SD) age was 29.4 (±3.4) years and preoperative corrected distance visual acuity (CDVA) was 0.36 (±0.32). Nine eyes had 1 break while 3 eyes had 2 breaks within 1 clock hour. Mean duration of operation was 11.7 (±1.8) min. No patient experienced major intraoperative complications, but one patient required reoperation. Mean CDVA 6 months postoperatively was 0.63 (± 0.21) (p < 0.05).